á¸¤IKMAH DALAM PERSFEKTIF ALQURAN - Tahir, Muhyiddin (State Institute of Islamic Studies (IAIN) Palu, 2012)
Abstract: The Qurâ€™an is admitted by Muslims as a collection of God's words which have been recorded in the form of a book. The word á¸¥ikmah is one of the words repeatedly stated in the Qurâ€™an, but the word will have its own meaning, when coupled with specific words in the Qurâ€™an. Therefore, the use of the word in the Qur'an should be interpreted and understood. That understanding can be extracted from the Qur'an itself, which is also considered the á¸¥ikmah because it is full of wisdom that should be applied, both in individual life and in the social life.Kata Kunci: hikmah, Alquran, mawÄâ€™iáº“, kenabian